Preliminary characterization of aluvial mining waste in the Madre de Dios region - Peru - Huamán-Paredes, Flora Elsa; Palma-Figueroa, Gregorio Urbano; Flores-del Pino, Lisveth (Revista Cubana de Química, 2020)
In the alluvial mining of Madre de Dios-Perú región, they use mercury in the gold extraction process, generating a solid waste called Arenas Negras. The objective of the work was the preliminary characterization of these sands that werecollected from different mining concessions, according to the soil sampling guideline of the Ministry of the Environment. The mercury metal was determined by atomic emission spectrophotometry, the physical parameters using the international methodology solid waste and phases with the conventional method using an X-ray Diffractometer. The Arenas Negras of high Madre de Dios revealed a total mercury value of more than 275 mg.Kg-1 of waste, while Inambari a value of 13,1 mg.Kg-1. An average difference of 137,79mg.Kg-1. The pH was between 7 and 6,5 and conductivities up to 0,01092 S.m-1. The phases identified in the arenas negras were mainly quartz, ilmenite, hematite and goethite.